A 2 Set-Up Binary Routley Semantics for Gödelian 3-Valued Logic G3 and Its Paraconsistent Counterpart G3\(_Ł^≤\) - Robles, Gemma; Méndez, José M. (Bulletin of the Section of Logic, 2022)
G3 is Gödelian 3-valued logic, G3\(_Ł^≤\) is its paraconsistent counterpart and G3\(_Ł^1\) is a strong extension of G3\(_Ł^≤\). The aim of this paper is to endow each one of the logics just mentioned with a 2 set-up binary Routley semantics.